Օսլո 2 համաձայնագիրը որպես պաղեստինյան հակամարտության կարգավորման հերթական քայլ - Հովհաննիսյան, Արտակ («Զանգակ - 97»)
In September 24, 1995 Israeli and Palestine Liberation Organization (PLO) officials meeting in Taba, Egypt, finalized agreement on the second stage of eventual Israeli withdrawal from Palestinian lands. Under the pact, which was officially signed on September 28 in Washington, D.C., Israeli forces were scheduled to be removed from 6 Arab cities and 400 villages in the West Bank by early 1996, after which elections would be held for a 82-member Palestinian council, which would possess legislative and executive power in the West Bank and Gaza. Special arrangements were agreed upon for the West Bank city of Hebron, where Israeli soldiers will remain to prolect the 450 Jewish settlers living there. Disagreement over the status of Hebron almost scuttled the agreement, and it took almost a week of non-stop negotiations between PLO leader \Yasir Arafat and Israeli Foreign Minister Shimon Peres to resolve the issue.
Keywords: Պատմություն; Քաղաքականություն